Natural Processes and Spatial Mobility In The Territory. Nuevo Santa Rosa, Cura Mori – Piura, With de Presence of El Niño Phenomenon 2017 - Sánchez, Rocío del Alba Álvarez (MAJ - Malaysia Architectural Journal, 2025)
The Bajo Piura, due to its low slope and proximity to the Piura River, is exposed to the flooding hazard due to the recurring presence of El Niño Phenomenon, on the northern Peruvian coast. Faced with this, the population that inhabits these territories, specifically, the community of Nuevo Santa Rosa, Cura Mori district, Piura Region, has put into practice seasonal mobility processes, and in recent years, the definitive resettlement, due to the pressure exerted by new agro-industrial investments to appropriate communal lands. Qualitative methodology is applied to the study with activities such as; walking and urban tours, interviews, workshops with children; that allow identifying conditions for the choice of the new place of occupation by the community. Based on Álvarez (2019), This way of inhabiting the territory, obeys to a construction of ancestral knowledge, and a vision and recognition of the place they inhabit, as a communal space. These practices are into the territorial approach, enunciated by Magnaghi (2011), Beuf (2017), Canziani (2017) and Bernex (2018) which considers the territory is a complex living organism, which is in constant movement and evolution, where relationships are built between human beings and the environment they inhabit. Thus, the collective practices of the population constitute a culturally learned response in relation to the physical environment that surrounds them and demonstrate a rationality in the form of occupation of the territory. The research identifies a new scenario where the population coexists with the agro-export companies that are their new neighbors.